2002
DOI: 10.1038/sj.ejcn.1601449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate weight loss on anginal symptoms and indices of coagulation and fibrinolysis in overweight patients with angina pectoris

Abstract: Objective: To evaluate the effects of moderate weight loss, in overweight patients with angina, on plasma coagulation, fibrinolytic indicies and pain frequency. Conclusions: A conventional dietetic intervention, resulting in 4% weight loss, offers the potential to reduce atherosclerotic and thrombotic risk, and to reduce pain frequency, in angina patients. Given the importance of this result in a public health context, these results indicate that this may be a fruitful area for future nutrition research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
(39 reference statements)
3
10
1
Order By: Relevance
“…Odds ratios for VTE risk related to overweight and obesity were consistent with those of previous studies [1]. This added validity to our results with [3,4]. Similar trends of a significant decrease of cardiovascular disease incidence [5], including coronary artery disease [6], were found by other authors.…”
supporting
confidence: 82%
“…Odds ratios for VTE risk related to overweight and obesity were consistent with those of previous studies [1]. This added validity to our results with [3,4]. Similar trends of a significant decrease of cardiovascular disease incidence [5], including coronary artery disease [6], were found by other authors.…”
supporting
confidence: 82%
“…Alcohol consumption thus seems to lead to a net increase in energy intake and therefore may contribute to hypercaloric diets and obesity in the general population. Studies have shown that body weight loss causes increased HDL-C (Williams, 2004) and decreased fibrinogen (Hankey et al, 2002). In our study, the increase in HDL-C and decrease in fibrinogen in the red wine group were significant different from the other three groups combined in defiance of the weight loss in the three groups.…”
Section: Discussionsupporting
confidence: 48%
“…Obese subjects tend to have impaired coagulative and fibrinolytic functions (Mertens and Van Gaal, 2002) and weight reduction has been shown to improve indices of coagulation and fibrinolysis in overweight subjects (Hankey et al, 2002). Although the precise mechanisms remain unclear, it is known that hyperhomocysteinemia activate the coagulation system (Fonesca et al, 1999).…”
Section: Discussionmentioning
confidence: 98%